Avaliação preliminar das helmintíases intestinais em cães do município de Viçosa, Minas Gerais - Junqueira del Carlo, Ricardo; Baracat de Araújo, Roberto; Batista de Assis, Carlos (Revista Ceres, 2025)
A total of 251 fecal samples of dogs was examined in research of dog intestinal helminths in Viçosa, Minas Gerais. The objectives were to determine the species of helminths and the frequency of their occurrence.